Relationship between the clinical assessment of maxillary and mandibular complete denture stability and denture-bearing area towards the patient’s satisfaction level - Ritonga, Putri Welda Utami; Prabakaran, Luveena Loshini (Padjadjaran Journal of Dentistry, 2018)
Introduction: The dentist’s evaluation of complete denture often differs from the patient’s evaluation. Dentists are more prioritising the clinical aspects of the dentures, such as vertical dimension, aesthetical, stability, and denture-bearing area, while patients are more prioritising their satisfaction based on aspects such as aesthetical, mastication, comfort, and phonetic ability. The purpose of this study was to determine the relationship between the stability of maxillary and mandibular denture-bearing area towards the complete denture patient’s satisfaction level. Methods: This study was a cross-sectional study with purposive sampling as the sampling method. The sample of this study was as much as 30 complete denture patient. The patients were interviewed using a questionnaire in each of the patient’s house, to obtain a more honest patient’s satisfaction assessment on the dentures, without being affected by any clinical environment and assessment. The interview was conducted before the clinical evaluation was performed. The statistical analysis was performed using the Fisher’s test. The stability of the denture-bearing area was evaluated clinically. Mastication ability and patient’s comfort were evaluated using a questionnaire. Result: A significant relationship was found between the stability of maxillary denture-bearing area towards mastication (p = 0.012), and the stability of mandibular denture-bearing area towards mastication (p = 0.029); while no significant relationship was found between the stability of maxillary denture-bearing area towards the patient’s comfort (p = 0,051), and the stability of mandibular denture-bearing area towards the patient’s comfort (p = 0,547). Conclusion: There was a relationship between the  stability of maxillary and mandibular denture-bearing area towards the patient’s masticatory satisfaction level. However, the relationship between the  stability of maxillary and mandibular denture-bearing area towards the patient’s comfort was not found.